Performance analysis of a hybrid lightweight vehicle with downsized engine - Karagoz, Yasin; Balci, Ozgun; Gezer, Onur; Kale, Sefa; Koten, Hasan (TAYLOR & FRANCIS INC, 2020)
Today, due to increased environmental concerns on NOx and PM emissions caused by diesel vehicles, researchers have focused on the development of hybrid engine vehicles. Therefore, an SI engine was chosen in the present study. In addition, an extra downsized single-cylinder engine model for hybrid system and a four-cylinder engine model for conventional system were selected with lightweight vehicle in order to investigate advantageous provided in crowded city traffic conditions. The models have three-way catalyst (TWC) and cold-start operation conditions. The result of the experiment using the theoretical model developed by us and the experimental results of the SI engine are verified by using a series hybrid drive system in a gasoline light-duty vehicle used today as a passenger car. According to obtained results, CO, HC, and NOx emissions of the four-cylinder gasoline fueled vehicle and single-cylinder series hybrid system were compared instantaneously for ECE, NEDC, and WLTC cycles. According to results, fuel consumption, CO, and HC decreased while NOx emissions increased.
Keywords: Hybrid vehicle; series hybrid system; vehicle model; lightweight vehicle; driving cycles; EMISSIONS; GAS; NOX; Energy & Fuels; Engineering; Environmental Sciences & Ecology